Current Concepts in Endoscopic Bladder Neck Injection: Combined Antegrade and Retrograde Endoscopic Injection of the Bladder Neck in Children with Neurogenic Bladder - Frank-Martin Haecker; Anja Mettler; Alexander Mack (MDPI AG, 2022)
Introduction: Urinary incontinence is common in patients with neurogenic bladder, and efficient management is an ongoing challenge. Besides open surgical procedures like bladder neck reconstruction, artificial sphincter implantation, or sling procedures, endoscopic bladder neck injections of bulking agents enable minimally invasive access with promising results. Several studies report on the effect of antegrade vs. retrograde endoscopic injection techniques. We report our preliminary experience of combined antegrade and retrograde endoscopic injection of the bladder neck in children with neurogenic bladder, in selected cases combined with intravesical Botox® injection. Methods: With the patient in lithotomy position, antegrade urethrocystoscopy was performed using a 9.5 Fr cystoscope. In parallel, percutaneous suprapubic bladder access introducing a second 9.5 Fr. cystoscope was accomplished. Four quadrant Dx/H injections were performed, with the two surgeons guiding each other by parallel endoscopy to the optimal localization for injection. In selected patients, the procedure was completed with transurethral intravesical Botox® injection. Results: A total of 6 children underwent the combined procedure (2/6 patients including intravesical Botox® injection). The mean follow-up was 15 months (range 3 to 48). 5 Patients experienced a significant improvement of urinary incontinence, however one patient demonstrated complete failure. Conclusions: Even if we present only preliminary results with a limited number of patients, we present a minimally invasive technique with encouraging results. In carefully selected patients, combined antegrade and retrograde endoscopic injection of the bladder neck is a useful tool to treat urinary incontinence.